Sub-Tenon's block reduces both intraoperative and postoperative analgesia requirement in vitreo-retinal surgery under general anaesthesia. - Farmery, A; Shlugman, D; Rahman, R; Rosen, P (2003)
BACKGROUND AND OBJECTIVE: We compared the effects of sub-Tenon's local anaesthetic block and placebo on peri-operative opioid requirement and cardiovascular stability and on postoperative pain, nausea and vomiting in patients undergoing vitreo-retinal surgery under general anaesthesia. METHODS: We studied 43 patients undergoing vitreo-retinal surgery under general anaesthesia in a randomized double blind study. Patients received a standard general anaesthetic followed by a sub-Tenon's injection of 4-5 mL of either bupivacaine 0.75% or saline. We recorded intraoperative invasive arterial pressure, then the incidence and severity of pain and of nausea and vomiting, for 24 h postoperatively. RESULTS: In the sub-Tenon's bupivacaine group, there was a significant reduction in the perioperative opioid use and a reduction in the frequency of bradycardia and hypertensive episodes, defined as a rise > 25% of baseline for a duration of > 3 min. The sub-Tenon's bupivacaine group also had significantly lower pain scores and nausea scores at 12 h, concomitant with a lower consumption of analgesia and antiemetics. CONCLUSIONS: This local anaesthetic technique is effective in vitreo-retinal surgery and can be safely applied to this population of patients regardless of axial length.